COLLABORATIVE LEARNING IN ENGLISH AND SCIENCE: ENHANCING LANGUAGE PROFICIENCY THROUGH GROUP ACTIVITIES - Abdugafforova Nozima (PEDAGOGS, 2024)
Annotation: This article discusses the benefits of collaborative learning in English language instruction, particularly through the integration of science-based group activities. By engaging in group work, students can develop language proficiency while enhancing their understanding of scientific concepts. The article explores various strategies for incorporating group learning themes in the classroom, including problem-solving tasks, project-based learning, and peer teaching. It emphasizes the importance of teamwork, communication, and critical thinking, offering practical examples for educators to implement in their lessons.